EFEKTIVITAS MEDIA FITER PASIR AKTIF DALAM MENURUNKAN KADAR MANGAN PADA AIR BERSIH di PT X - Iqbal, Muhamad; Mulyati, Sri Slamet (Poltekkes Kemenkes Bandung, 2025)
Clean water pollution at PT X is caused by manganese levels that exceed the safe limit, reaching 2.01 mg/L, which has the potential to endanger the health of employees. This research aimed to evaluate the effectiveness of active sand filter media thickness in reducing manganese levels in clean water at PT X. This research was an experiment with a post-test with a control group design. This type of experiment involves testing certain treatments, with three variations in the thickness of the active sand filter media (60cm,80cm, and 100cm), as well as six repetitions for each treatment. Active sand is prepared by washing, drying, and heating at a temperature of 700-750°C for 2 hours. After use, the sand media is cleaned via backwash to maintain optimal performance during testing. The examination results using the spectrophotometer method showed that a thickness of 100cm was the most effective, reducing manganese levels by up to 97.67%, followed by a thickness of 80cm by 86.19%, and thickness of 60cm with a reduction of 47.97%. The ANOVA test indicated a significant difference in the reduction of manganese levels between the control and treatment groups, with a thickness of 100 cm giving significant results (F=22.054, p=0.003) and a thickness of 60 cm showing the highest F-value (F=481.201). The filter media thickness plays an important role in the effectiveness of manganese reduction, with a thickness of 100 cm proving optimal. It is recommended to use a thickness of 100 cm to ensure clean water quality at PT X.